Ploidy, sex and crossing over in an evolutionary aging model - Lobo, M. P.; Onody, R. N. (Elsevier B.V., 2006)
Nowadays, many forms of reproduction coexist in nature: Asexual, Sexual, apomictic and meiotic parthenogenesis, hermaphroditism and parasex. The mechanisms of their evolution and what made them successful reproductive alternatives are very challenging and debated questions. Here, using a simple evolutionary aging model, we give I possible scenario. By studying the performance of Populations where individuals may have diverse characteristics-different ploidies, sex with or without crossing over, as well as the absence of sex-we find all evolution sequence that may explain why there are actually two major or leading groups: Sexual and asexual. We also investigate the dependence of these characteristics on different conditions of fertility and deleterious mutations. Finally, if the primeval organisms oil Earth were, in fact, asexual individuals we conjecture that the sexual form of reproduction could have more easily been set and found its niche during a period of low-intensity mutations. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: population dynamics; biological evolution; sexual and asexual reproduction; crossing over